FAMILY LONCHAEIDAE - Fernandes, Juliana Morgado; Couri, Márcia Souto (Zootaxa, 2016)
This family was poorly known in the Neotropical region, mainly in Colombia. However, recent studies increased its knowledge with new distribution records. This catalogue presents 44 species distributed in three genera.